Policy Advice to Asia in the COVID-19 Era - Rhee, Changyong; Svirydzenka, Katsiaryna (Washington, D.C. : International Monetary Fund, 2021)
The Asia-Pacific region was the first to be hit by the COVID-19 pandemic; it put a strain on its people and economies, and policymaking became exceptionally difficult. This departmental paper contains the assessment of the key challenges facing Asia at this critical juncture and policy advice to the region both to address the current challenges and to build the foundations for a more sustainable and inclusive future. The paper focuses on (1) adjusting to the COVID-19 shock, (2) using unconventional policies when policy space is limited, (3) dealing with debt, and (4) helping the vulnerable and greening the recovery. The paper first presents the different ways countries are adjusting to the COVID-19 shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet